2020
DOI: 10.1080/13803395.2020.1843603
|View full text |Cite
|
Sign up to set email alerts
|

The downsized hand in personal neglect

Abstract: Objective: Personal neglect (PN) refers to a form of hemi-inattention toward the contralesional body space and it usually occurs following a right brain lesion. Recent studies suggest that PN indicates a disorder of body representation. Specifically, patients with PN show difficulties in identifying differences between left and right hands and have an altered visuospatial body map, which is associated with disrupted mental body representations. However, the metric representation of the body, and in particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…To date, few group studies have investigated the neuroanatomical correlates of PN, mainly because this condition has been considered as a symptom of a more general spatial neglect syndrome and has been investigated in the literature primarily with reference to extrapersonal space (Committeri et al 2018 and Caggiano and Jehkonen 2018 for review). The sample of PN patients in these previous studies ranges from 5 to 30 (Bisiach et al 1986a ; Azouvi et al 2002 ; Buxbaum et al 2004 ; Committeri et al 2007 ; Baas et al 2011 ; Rousseaux et al 2015 ; Caggiano et al 2020 ) and the impact of other clinical variables has not been directly investigated. This makes it difficult to disambiguate the lesions that specifically impact on PN and those that are associated with other co-occurrent symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, few group studies have investigated the neuroanatomical correlates of PN, mainly because this condition has been considered as a symptom of a more general spatial neglect syndrome and has been investigated in the literature primarily with reference to extrapersonal space (Committeri et al 2018 and Caggiano and Jehkonen 2018 for review). The sample of PN patients in these previous studies ranges from 5 to 30 (Bisiach et al 1986a ; Azouvi et al 2002 ; Buxbaum et al 2004 ; Committeri et al 2007 ; Baas et al 2011 ; Rousseaux et al 2015 ; Caggiano et al 2020 ) and the impact of other clinical variables has not been directly investigated. This makes it difficult to disambiguate the lesions that specifically impact on PN and those that are associated with other co-occurrent symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Comb and Razor/Compact), the two subtests are highly correlated (McIntosh et al 2000 ; Beschin and Robertson 1997 ) and several previous studies have used only one subtest (e.g. Moro et al 2022 ; Moro and Besharati 2021 ; Pacella et al 2019 ; D’Imperio et al 2017a , b ; Caggiano et al 2020 ). The choice of the Comb subtest guarantees the possibility of using the same task for both males and females and to exclude any effects of sensory deficits (as the upper part of the face has bilateral innervation).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hand distortions are assumed to be quite robust and resistant to changes on the type of instructions (Longo 2018 ), task modality (Ambroziak et al 2018 ; Peviani and Bottini 2018 ), or hand orientation (e.g., Longo and Haggard 2010 ; Saulton et al 2016 ). However, some studies have shown how the extent of the distortion can be modulated by multisensory information, such as positional changes (Longo 2015 ); vision (Longo 2014 ); tool use and type of action (Romano et al 2019 ); sound (Tajadura-Jiménez et al 2017 ), and attentional impairments (Caggiano et al 2020 ), confirming that the representation of the body is highly malleable (Ambron et al 2018 ; Medina and Coslett 2016 ; Medina et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis at the basis of the present study is that PN is a disconnection syndrome which is not associated with discrete grey matter lesions, but instead involves a right hemisphere network of cortical However, a certain degree of ambiguity persists in these results, for several reasons. Firstly, to date neuroanatomical studies on PN have been conducted on small samples, with a maximum of 30 patients presenting with the symptoms; these have often been compared to left hemisphere damaged patients (Azouvi et al 2002;Buxbaum et al 2004;Committeri et al 2007;Baas et al 2011;Rousseaux et al 2015;Caggiano et al 2020). Furthermore, the results of these studies focused on the identi cation of discreet cortical lesions and did not analyse white matter disconnections in a speci c way.…”
Section: Introductionmentioning
confidence: 99%